1999
DOI: 10.1093/treephys/19.7.467
|View full text |Cite
|
Sign up to set email alerts
|

Limitation of leaf carbon gain by stomatal and photochemical processes in the top canopy of Macaranga conifera, a tropical pioneer tree

Abstract: Diurnal changes in gas exchange and chlorophyll fluorescence were measured in the top canopy leaves of the tropical rainforest tree species, Macaranga conifera (Zoll.) Muell. Arg. during a drought year. Maximum values of net photosynthetic rate (P(n), 10 &mgr;mol m(-2) s(-1)) and stomatal conductance (g(s), 0.2 mol m(-2) s(-1)) were found in east-facing leaves in early morning. After 1000 h, both P(n) and g(s) decreased. Minimum daytime values of P(n), g(s), and photosystem II (PSII) quantum yield (DeltaF/F(m)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1
8

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 38 publications
5
53
1
8
Order By: Relevance
“…L s increased all along in morning and then decreased after 12:00, suggesting that stomatal limitation to photosynthesis was dominating in morning but non-stomatal limitation was dominating in afternoon; we thought perhaps after the midday depression of photosynthesis the plant needs longer time to repair itself. Low P N at midday was the result of both a reduction in the photochemical process and an increase in stomatal limitation (Ishida et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…L s increased all along in morning and then decreased after 12:00, suggesting that stomatal limitation to photosynthesis was dominating in morning but non-stomatal limitation was dominating in afternoon; we thought perhaps after the midday depression of photosynthesis the plant needs longer time to repair itself. Low P N at midday was the result of both a reduction in the photochemical process and an increase in stomatal limitation (Ishida et al 1999).…”
Section: Discussionmentioning
confidence: 98%
“…As leaf temperatures rise, evaporative demand increases, causing stomata to close to reduce water loss and thereby decrease photosynthetic rates (Doughty & Goulden 2008, Lloyd & Farquhar 2008). Experiments and eddy-covariance flux measurements suggest that photosynthesis in present-day lowland tropical forests may be approaching, but has not passed, its high-temperature threshold on the warmest days (Doughty & Goulden 2008, Goulden et al 2004, Graham et al 2003, Ishida et al 1999, Loescher et al 2003.…”
Section: Photosynthesismentioning
confidence: 99%
“…Points of inflection typically occur at 35-45°C for many hightemperature-adapted plants (Berry & Bjö rkman 1980). Temperatures of leaves at the top of the canopy may be at the bottom of this range around midday at some locations on some days, and post-midday declines in photosynthesis have been documented (Ishida et al 1999). However, separating the effects of high temperatures and daytime stomatal closure, owing to inadequate water supply, on photosynthetic rates is difficult.…”
Section: (I) Temperature Effects On Photosynthesismentioning
confidence: 99%
“…However, separating the effects of high temperatures and daytime stomatal closure, owing to inadequate water supply, on photosynthetic rates is difficult. An experiment artificially heating leaves in the early morning and cooling leaves at midday showed that both temperature and stomatal closure depressed photosynthetic rates at midday of an in situ pioneer tree (Ishida et al 1999). In another experiment seedlings of four dipterocarp species were exposed to increasing temperatures.…”
Section: (I) Temperature Effects On Photosynthesismentioning
confidence: 99%